Linear Network Representation Applied to evolving of the Architecture and Weights of Neural Network (Journal of the College of Basic Education, 2022)
Evolutionary computation is a class of global search techniques based onthe learning process of a population of potential solutions to given problem thathas been successfully applied to a variety of problems. In this paper a new approach to design of the neural networks based on evolutionary computation is present. A linear chromosome representation of the network are used by genetic operators, which allow the evolution of the architecture and weights simultaneously without the need of local weights optimization. This paper describes the approach, the operators and reports results of the application of this technique to several binary classification problems.